The Treasury Market Practices Group: Creation and early initiatives - Kenneth D. Garbade; Frank M. Keane (Federal Reserve Bank of New York, 2017)
Modern money and capital markets are not free-form bazaars where participants are left alone to contract as they choose, but rather are circumscribed by a variety of statutes, regulations, and behavioral norms. This paper examines the circumstances surrounding the introduction of a set of norms recommended by the Treasury Market Practices Group (TMPG) and pertinent to trading in U.S. government securities. The TMPG is a voluntary association of market participants that does not have any direct or indirect statutory authority; its recommendations do not have the force of law. The recommendations do, however, carry the cachet of respected market participants and are targeted to behaviors that are widely acknowledged to impinge on market liquidity and that risk damaging the reputation of the market.
Keywords: E58; G20; N22; 330; Treasury Market Practices Group; behavioral norms; fails charge; dealer time; margin